The 2021 Ms 6.0 Luxian (China) Earthquake: Blind Reverse‐Fault Rupture in Deep Sedimentary Formations Likely Induced by Pressure Perturbation From Hydraulic Fracturing. Issue 7 (7th April 2023) - Zhao, Yingwen; Jiang, Guoyan; Lei, Xinglin; Xu, Caijun; Zhao, Bin; Qiao, Xuejun
Abstract: To resolve the occurrence mechanism of the Luxian earthquake occurred near an active hydraulic fracturing well pad on 15 September 2021, we first use seismic waveforms to invert the focal mechanism solution and centroid depth, and then utilize Sentinel‐1 Synthetic Aperture Radar images and Global Navigation Satellite System observations to determine the seismogenic fault and slip distribution. Our results show that the Luxian event ruptured a previously‐unmapped southwest‐dipping reverse fault intersecting with one horizontal well of the well pad. Major slip occurred below the shale gas bed (∼4 km deep) but above the crystalline basement (∼7 km deep). Further analyses on preseismic surface deformation initiated in the northeast of the event reveal that pore pressure near the hypocenter was increased by ∼4.5 MPa. Consequently, fracking fluid injected through the horizontal well and other wells of nearby pads likely flowed directly into the fault zones and prompted the occurrence of the Luxian earthquake. Plain Language Summary: Due to huge casualties and property losses, the Ms 6.0 Luxian earthquake aroused wide public concern. Beyond that, at 0.85 km south of the epicenter, there is a hydraulic fracturing (HF) well pad (H79) that was operating before the earthquake occurrence. Therefore, people suspect that there was some relationship between the event and HF operations. We here jointly use seismic waveforms of regional permanent stations, Sentinel‐1 Synthetic Aperture Radar images, and Global Navigation Satellite System observations to determine the location and 3D geometry of the source fault. We find the fault intersecting with one horizontal well of the nearby pad, indicating that fracking fluid can flow directly into the fault zones and cause pressure perturbation with magnitudes comparable to the minimum principal stress. In addition, we also find preseismic deformation around the epicenter initiated after 29 May 2021. The deformation is likely linked to accumulation of fracking fluid injected during the drilling and HF operations of other pads. Further modeling reveals that the fluid accumulation increased pore pressure by ∼4.5 MPa near the hypocenter. The source fault likely suffered pressure diffusion before the operation of well pad H79 and was eventually reactivated by pressurization directly linked to HF stimulation. Key Points: The Luxian earthquake ruptured an unmapped south‐dipping reverse fault with major slip occurred in deep sedimentary formations Preseismic surface deformation analyses indicate that fracking fluid accumulation likely caused pressure increase near the hypocenter The source fault, intersecting with one horizontal hydraulic fracturing well, was likely reactivated by direct fault‐zone pressurization